Job access after leaving education: A comparative analysis of young women and men in rural Germany - İlkay Unay-Gailhard (Journal of Youth Studies, 2016)
Rural labour markets for youth are an interesting research area for labour force transition studies because gender differences begin to appear with the out-migration that leads to a shortage of young women in Europe. Whilst existing studies provide insight into this migration flow, little is known about the young women and men who remain in the labour force in rural areas. The aim of this study is to provide insight into the determinants of job access after leaving education in Germany among the young population aged 15–29 based on the Labour Force Survey of 2002–2009. First, an empirical analysis of student to employment flow in rural areas with respect to social position (degree discipline, age, and socio-professional category) has been conducted. Second, gender-specific multinomial logit models are used to estimate the determinants of access to a first job without a long-term unemployment spell. The results suggest that there are substantive differences in student to employment flow between female and male samples for the variables urbanisation degree of residence (rural, urban, and peri-urbain) and marital status. Contrary to our expectations, living in rural areas does not suggest a significant negative effect in accessing a job within a year. In line with previous studies, being married has a negative influence on female graduates but is positive for their male counterparts.
Keywords: 330; school-to-work transition; rural labour force; transitional labour market approach; gender; Labour Force Survey; rural areas; Germany